Ariella Aïsha Azoulay, Potential History: Unlearning Imperialism (London: Verso, 2019), 656 pp, ISBN 9781788735711 - van Laun, Bianca (Kronos: Southern African Histories, 2021)
Potential History: Unlearning Imperialism is a call to de-imperialise museums, archives and the discipline of history itself. Photographic theorist Ariella Aïsha Azoulay invites us to return to a moment before ‘original’ imperial violence occurred and set to work from there. It is an endeavour to think against and before imperialism, while simultaneously recognising that we are always already conditioned by it. Potential History asks us to unlearn imperial modes of thinking, the archive, the museum, the document, and history itself. To unlearn imperialism, Azoulay suggests that we reject a temporality that consigns violence to the distant past and instead attend to its still-present potentialities. She proposes a methodological approach to historical and archival materials that refuses to consign them to an irretrievable past. She is not suggesting that we counter the work of imperialism with alternative narratives, but rather, that we pursue an ongoing process of unlearning and undoing of the knowledge structures that sought to fix events, timelines and facts.